Concise Review: Review and Perspective of Cell Dosage and Routes of Administration From Preclinical and Clinical Studies of Stem Cell Therapy for Heart Disease. (18th December 2015) - Golpanian, Samuel; Schulman, Ivonne H.; Ebert, Ray F.; Heldman, Alan W.; DiFede, Darcy L.; Yang, Phillip C.; Wu, Joseph C.; Bolli, Roberto; Perin, Emerson C.; Moyé, Lem; Simari, Robert D.; Wolf, Ariel; et al.
Abstract : An important stage in the development of any new therapeutic agent is establishment of the optimal dosage and route of administration. Inconsistent findings have been reported regarding the relationship between the cell dose and clinical benefit. The present study summarizes the data regarding the optimal cell dosage and route of administration from studies of stem cell therapy for heart disease and offers a perspective on future directions. Abstract : An important stage in the development of any new therapeutic agent is establishment of the optimal dosage and route of administration. This can be particularly challenging when the treatment is a biologic agent that might exert its therapeutic effects via complex or poorly understood mechanisms. Multiple preclinical and clinical studies have shown paradoxical results, with inconsistent findings regarding the relationship between the cell dose and clinical benefit. Such phenomena can, at least in part, be attributed to variations in cell dosing or concentration and the route of administration (ROA). Although clinical trials of cell‐based therapy for cardiovascular disease began more than a decade ago, specification of the optimal dosage and ROA has not been established. The present review summarizes what has been learned regarding the optimal cell dosage and ROA from preclinical and clinical studies of stem cell therapy for heart disease and offers a perspective on future directions. Significance: Preclinical and clinical studies on cell‐based therapy for cardiovascular disease have shown inconsistent results, in part because of variations in study‐specific dosages and/or routes of administration (ROA). Future preclinical studies and smaller clinical trials implementing cell‐dose and ROA comparisons are warranted before proceeding to pivotal trials.